Spray Dried Nanoparticle for Pulmonary Delivery: Current Developments and Future Perspectives - Pawara, Yuvraj Sakharam; Mahajan, Hitendra Shaligram (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim: The study aims to comprehensively review advancements in spray-dried nanoparticles for pulmonary drug delivery. It focuses on understanding current techniques, nanoparticle types and applications. Additionally, it aims to identify challenges, assess developments critically and propose future perspectives. The research explores strategies to enhance nanoparticle efficiency, safety and targeted lung delivery. The ultimate goal is to provide valuable insights guiding researchers, pharmaceutical scientists and healthcare professionals in optimizing the design for improved therapeutic strategies in respiratory diseases, leading to better patient outcomes. Background: Dry Powder Inhalers (DPIs) have emerged as a popular method for delivering therapeutic aerosols to the lungs, targeting respiratory conditions including lung cancer, asthma, COPD, cystic fibrosis and pulmonary arterial hypertension. With their huge surface area for absorption, lower metabolic activity than other organs, many capillaries and thin air-blood barrier, the lungs will be significant advantages for systemic medication administration. The particle size shall play a significant role in their deposition in the respiratory tract. Conclusion: A promising formulation technique that combines the advantages of nanotherapeutics and the aerodynamics necessary for effective pulmonary medication administration is combined by controlled agglomeration of Nanoparticles (NPs) into micron-sized clusters. For the creation of microparticles from colloidal solutions containing NPs, spray drying is a flexible approach that is frequently used. The formulation and process characteristics of NP-based drug delivery systems, as well as improvements in spray drying technology. To promote their commercialization, future research should concentrate on scaling up the manufacturing of NP agglomerates and establishing downstream processing strategies.
Keywords: Dry powder inhaler; pulmonary drug delivery; spray drying; drug nanoparticle